Analisis Titik Daerah Rawan Kecelakaan Tertinggi Jalan Tol Surabaya – Gempol Dengan Metode Equivalent Accident Number (EAN) Serta Upaya Penanganannya - Tasya Riskiani (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2025)
The Surabaya–Gempol Toll Road is a strategic transportation corridor in East Java that supports both the movement of people and the distribution of goods. As traffic volume continues to increase, the risk of traffic accidents along this route has also risen. This study aims to identify accident-prone areas (black spots) and evaluate road users perceptions regarding the causes and handling of incidents, particularly at KM 15–16 of Lane B. A quantitative approach was employed in this research. The Equivalent Accident Number (EAN) method was used to determine accident-prone locations, while user perceptions were assessed using a Likert scale through distributed questionnaires. Prior to analysis, the instrument was tested for validity and reliability using SPSS, involving a total of 30 respondents. The analysis results indicate that the accident-prone area is located at KM 15–16 of Lane B, with KM 15.600 identified as the most critical point. Perceptions suggest that poor lighting and driver fatigue are the primary contributing factors to accidents. Respondents viewed incident handling as fairly adequate, although aspects such as emergency services and reporting systems require improvement. This study recommends enhancements in safety infrastructure and traffic management in high-risk areas.